(untitled) (Bangladesh Journal of Zoology, 2020)
During the study period a total 351 wasp was collected from three different areas of Dhaka city viz Curzon Hall, Ramna Park and Sher-e-Bangla Agricultural University from October 2017 to May 2019. Among them 14 species belonging to four families- Ampulicidae, Sphecidae, Vespidae and Scoliidae were identified. The species were Ampulex compressa, Chalybion bengalense, Scolia sp., Laeviscolia frontalis, Delta esuriens, Rhynchium quinquecintum, Antodynerus flavescens, Parapolybiavaria sp., Ropalidia marginata, Polistes olivaceus, Polistes watti, Polistes stigma, Vespa tropica, and Vespa affinis. Standard taxonomic keys and sharp perception of outside morphology like head, wing venation, antennal sort, physical coloration etc. of the wasps were examined to identify them. Maximum of the distinguished species were beneath the family vespidae (72%). In the present study, it was observed that the maximum number of wasps were collected in May (29.63%). The richness of wasp species was more plenteousin Curzon Hall area (47.58%) than the Sher-e-Bangla Agricultural University area (40.17%) and was less abundant in Ramna park (12.25%). The main reason for finding more richness of wasp species in Curzon Hall area was the presence of various types of hedging plants than other two areas as the wasps were found to prefer hedging plants for foraging. It was also observed that Polistes olivaceus (21.93%) was the most abundant and Chalybion bengalense was (0.85%) the least abundant species in the study areas. Bangladesh J. Zool. 48(1): 37-44, 2020